Initial central venous pressure could be a prognostic marker for hemodynamic improvement of polymyxin B direct hemoperfusion: a retrospective cohort study. Issue 1 (December 2016) - Yamada, Hiroyuki; Tsukamoto, Tatsuo; Narumiya, Hiromichi; Oda, Kazumasa; Higaki, Satoshi; Iizuka, Ryoji; Yanagita, Motoko; Deguchi, Masako
Abstract Background Direct hemoperfusion with polymyxin B-immobilized fiber column (PMX-DHP) could improve the hemodynamic status of septic shock patients. As PMX-DHP is an invasive and costly procedure, it is desirable to estimate the therapeutic effect before performing the therapy. However, it is still unclear when this therapy should be started and what type of sepsis it should be employed for. In this study, we retrospectively examined the clinical effect of patients treated with PMX-DHP by using central venous pressure (CVP). Methods Seventy patients who received PMX-DHP for septic shock during the study period were recruited and divided into a low CVP group (n  = 33, CVP < 12 mmHg) and a high CVP group (n  = 37, CVP≧12 mmHg). The primary endpoint was vasopressor dependency index at 24 hours after starting PMX-DHP, and the secondary endpoint was the 28-day survival rate. Additionally, we performed a multivariate linear regression analysis on the difference in the vasopressor dependency index. Results The vasopressor dependency index significantly improved at 24 h in the low CVP group (0.33 to 0.16 mmHg−1 ;p  < 0.01) but not in the high CVP group (0.43 to 0.34 mmHg−1 ;p  = 0.41), and there was a significant difference between the two groups in the index at 24 h (p  = 0.02). The 28-day survival rate was higher in the low CVP group (79 vs. 43 %;p  < 0.01). Multivariate linear regression analysis showed that CVP (p  = 0.04) was independently associated with the difference in the vasopressor dependency index. Conclusions Our study indicates that the clinical effect of PMX-DHP for septic shock patients with higher CVP (≧12 mmHg) might be limited and that the initial CVP when performing PMX-DHP could function as an independent prognostic marker for the hemodynamic improvement.